Management and Prognostic Factors for Thyroid Carcinoma Showing Thymus-Like Elements (CASTLE): A Case Series Study - Gao, Rui; Jia, Xi; Ji, Ting; Feng, Jinteng; Yang, Aimin; Zhang, Guangjian (Frontiers in Oncology, 2018)
Introduction: This study aims to identify the prognostic factors that influence therapeutic modalities for thyroid carcinoma showing thymus-like differentiation (CASTLE). Materials and Methods: Reported studies with CASTLE patients published between 2004 and 2018 were retrieved from a cross-database literature search. Three patients treated in our institute were also included as one case series. Standardized data collection was performed; data pertaining to clinical stages, treatment regimens, and survival time were collected and statistically analyzed. Results: Up to 26 case series of CASTLE were selected, including 51 males and 38 females with a median age of 48 years. Follow-up time ranged from 2 to 362 months and the median survival time was 158.03 months. Lymph node metastasis and tumor invasion of adjacent tissue both showed a significant negative effect on survival (p=0.001 and 0.013, respectively). Radiotherapy significantly improved survival (p=0.034), while neck dissection significantly prolonged survival only in patients with extrathyroidal extension (p=0.043). Conclusions: Extrathyroidal infiltration and nodal metastasis are important factors in cancer outcomes. Radiation therapy appears to be important for better outcomes in CASTLE patients, and neck dissection is recommended for patients with extrathyroidal extension.